Narrative exploration of cultural ecosystem services in the ravines of Moyobamba - Linarez Miranda, Jesus Ricardo; Ugaz Vasquez, Delvin Jhilmar; Arévalo Lazo, Cinthya (Frontiers in Built Environment, 2025)
The urban ravines of Moyobamba, despite being considered natural spaces, are fundamental spaces for citizen participation, related to a sociocultural issue of local identity, social interaction and community welfare. Despite this, their current state has been affected, which could lead to a negative perception of the uses of these spaces. Therefore, this research analyzes the articulation of the cultural ecosystem services (CES) of the ravines and their level of conservation and through a mixed method, combining quantitative and qualitative approach, through semi-structured interviews to residents and experts on the subject of conservation of the ravines and the perception of their valuation was evaluated, in addition, through direct observation and documentary review, the analysis of their current physical state was made. It was found that the residents who live near the ravines or make use of them, value these spaces for a sense of relevance, promoting social interaction that offer opportunities for ecotourism and recreational activities. However, it was identified that the physical condition presents moderate and severe environmental deterioration, which has reduced the influx of visitors and the quality of the residents' experience. The results show that the ravines should be preserved for their ecological, cultural and social condition. The loss of spatial quality limits activities and reduces the positive impact of community participation. It is recommended that public conservation policies be strengthened to increase public awareness to ensure the valuation of these ecosystems and the legacy for future generations.